Enabling Private Sector Growth in Menya and Assiut, Egypt - World Bank (World Bank, Washington, DC, 2021)
Egypt has considerable potential to become a regional trade hub. A key challenge is how to leverage this potential to achieve inclusive and sustainable growth that benefits the country’s population at large. In alignment with Egypt’s decision to expand the Upper Egypt Local Development Program (UELDP) from an initial focus on Sohag and Qena to also include Menya and Assiut, this paper focuses on identifying opportunities and barriers to realizing inclusive and sustainable growth in these two governorates. Menya is the fourth-lowest and Assiut the fifth-lowest productive governorates in Egypt as measured by gross value added per capita. There is thus a pressing need for measures to promote inclusive growth and competitiveness in the two governorates The paper aims to inform the deliberations of the governorates recently established Economic Councils, as well as the continuous sub-sector specific public private dialogue, which forms part of UELDP. This paper thus serves as a starting point, and forth-coming dialogue could give rise to follow-on in-depth studies of sub-sectors of high priority to the governorates. Indeed, cluster competitiveness initiatives which focus on resolving sub-sector specific constraints are a part of the UELDP.